CircRNAs: a novel potential strategy to treat breast cancer - Chen, Pangzhou; Zhang, Jinhui; Wu, Song; Zhang, Xiaoyu; Zhou, Wen; Guan, Ziyun; Tang, Hailin (Frontiers in Immunology, 2025)
Breast cancer is among the most prevalent malignant tumors worldwide, with triple-negative breast cancer (TNBC) being the most aggressive subtype and lacking effective treatment options. Circular RNAs (circRNAs) are noncoding RNAs that play crucial roles in the development of tumors, including breast cancer. This article examines the progress of research on circRNAs in breast cancer, focusing on four main areas: 1) breast cancer epidemiology, classification, and treatment; 2) the structure, discovery process, characteristics, formation, and functions of circRNAs; 3) the expression, mechanisms, clinical relevance, and recent advances in the study of circRNAs in breast cancer cells and the immune microenvironment, particularly in TNBC; and 4) the challenges and future prospects of the use of circRNAs in BC research.